From Orphan Phage to a Proposed New Family-The Diversity of N4-Like Viruses - Johannes Wittmann; Dann Turner; Andrew D. Millard; Padmanabhan Mahadevan; Andrew M. Kropinski; Evelien M. Adriaenssens (MDPI AG, 2020)
Escherichia phage N4 was isolated in 1966 in Italy and has remained a genomic orphan for a long time. It encodes an extremely large virion-associated RNA polymerase unique for bacterial viruses that became characteristic for this group. In recent years, due to new and relatively inexpensive sequencing techniques the number of publicly available phage genome sequences expanded rapidly. This revealed new members of the N4-like phage group, from 33 members in 2015 to 115 N4-like viruses in 2020. Using new technologies and methods for classification, the Bacterial and Archaeal Viruses Subcommittee of the International Committee on Taxonomy of Viruses (ICTV) has moved the classification and taxonomy of bacterial viruses from mere morphological approaches to genomic and proteomic methods. The analysis of 115 N4-like genomes resulted in a huge reassessment of this group and the proposal of a new family "Schitoviridae", including eight subfamilies and numerous new genera.